Rearrangement in the Synthesis of Annulated Lactams Starting from Benzothiazines. Issue 28 (22nd August 2013) - Stalling, Timo; Saak, Wolfgang; Martens, Jürgen
Abstract: The conversion of methoxyamides based on iminic 1, 4‐benzothiazines has led to three different products depending on the substitution pattern. On the one hand, different types of unknown lactam systems with and without a rearrangement under ring contraction of the benzothiazine substructure were selectively obtained. In this investigation, annulated lactams without ring contraction were formed by oxidation of the sulfide group to a sulfone group in the benzothiazine skeleton. On the other hand, benzothiazoles, which are oxidation products, were isolated. The structures of all types of lactams were verified by X‐ray diffraction. Abstract : Depending on the substituents both on the phenyl ring and on the imine skeleton, the heteroatom in the ring, and the Lewis acid used, one of the presented final products was formed selectively in a two‐step sequence. As part of the lactamization reaction, a new rearrangement through ring contraction was found. The structures of the lactams were verified by X‐ray diffraction.